HUBUNGAN ANTARA PERSONAL HYGIENE DENGAN ANGKA KEJADIAN PEDICULOSIS CAPITIS PADA SANTRIWATI PONDOK PESANTREN PANCASILA BENGKULU TAHUN 2018 - Sudarsono Sudarsono; Sarita Miguna (Universitas Batam, 2019)
Pediculosis capitis is a skin or head hair infestation caused by Pediculus humanus var. Capitis. Pediculosis capitis mainly affects young children and some factors help spread Pediculosis capitis, namely socio-economic, level of knowledge, poor hygiene conditions, the density of dwellings such as boarding schools. This research method is a quantitative study with an observational analytic study with a cross-sectional approach, assessing the level of personal hygiene then relating it to the incidence of Pediculosis capitis. Data collection was carried out in August 2018. The population was 205 female students. The sample size was 127 female students using a simple random sampling technique. The statistical test used was the chi-square test using a 95% confidence level. A total of 127 respondents who met the inclusion criteria found female students with positive personal hygiene positive Pediculosis capitis infested with 50 respondents (79.4%) while female students with poor personal hygiene who were positive were infested with Pediculosis capitis as many as 63 respondents (98.4%). Students with good personal hygiene who were not infested with Pediculosis capitis were 13 respondents (20.6%) while students with poor personal hygiene who were not infested with Pediculosis capitis were 1 respondent (1.6%). Chi-square statistical test results obtained p = 0.002 (p <0.05) so that Ha is accepted and Ho is rejected. There is a significant relationship between Personal Hygiene with the incidence of Pediculosis capitis in Bengkulu Pancasila Islamic Boarding School students in 2018.